PENGARUH MODEL PEMBELAJARAN CORE (Connecting, Organizing, Reflecting, Extending) TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN DISPOSISI MATEMATIS PESERTA DIDIK KELAS VIII DI SMP SWASTA AL- MANAR - Ade Nur Triyani; Siti Maysarah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research is an experimental study with research objectives: 1) to determine the influence of CORE learning models (connecting, organizing, Reflecting, extending) on the mathematical creative thinking skills of students. 2) to find out the influence of CORE learning models (connecting, organizing, Reflecting, extending) on the mathematical disposition of students. The entire research population of the students of the First High School (SMP) Private Al-Manar in Medan Johor. The research sample is a private junior high school student of Al-Manar Medan Johor class VIII who totaled 126 people. The research method used is experiments with the Pre Test and Post Test research design to determine the initial capabilities and end abilities of the students. Data collection using mathematical ability test instruments, critical thinking skills tests, and mathematical dispositioned cartoon sheets. Hypothesis test analysis technique uses test-t paired. The results of the study are: 1) There is an influence of CORE learning model (Connecting, Organizing, Reflecting, Extending) on students’ creative thinking skills. This is in line with the hypothesis test results where t calculate > t table 3, 84 > 2.01 with Ho test criteria rejected and Ha accepted. 2) There is an influence of CORE learning model (Connecting, Organizing, Reflecting, Extending) on student mathematical disposition. This is in line with the hypothesis test results where t calculate > t table is 3, 95 > 2.01 with Ho test criteria rejected and Ha accepted. From the results of the analysis obtained findings that there are differences in mathematical learning outcomes with students taught through CORE learning models with learners taught through conventional learning models, as well as learning outcomes taught by CORE learning models higher than learners taught by conventional learning models